2011
DOI: 10.1007/s12583-011-0165-x
|View full text |Cite
|
Sign up to set email alerts
|

Melt evolution above a spontaneously retreating subducting slab in a three-dimensional model

Abstract: Dehydration of the subducting slab favors the melting of the surrounding mantle. Water content and melt evolution atop a spontaneously retreating subducting slab are reported in a three-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…All model boundaries are free slip, except for the lower one that is permeable. More detailed information about numerical modelling approach and material properties are given in Zhu et al 28 and Supplementary Table S2. An oceanic geotherm 29 defines the initial temperature field of the oceanic plates.…”
Section: Methodsmentioning
confidence: 99%
“…All model boundaries are free slip, except for the lower one that is permeable. More detailed information about numerical modelling approach and material properties are given in Zhu et al 28 and Supplementary Table S2. An oceanic geotherm 29 defines the initial temperature field of the oceanic plates.…”
Section: Methodsmentioning
confidence: 99%
“…Although foundering is probably an important mechanism in some places [ DeBari and Sleep , ; Kelemen et al ., ], recent studies have shown that felsic material may also detach from the slab because of the intrinsic buoyancy of the sediment layer itself [ Currie et al ., , Behn et al ., , Hacker et al ., ; Miller and Behn , ] and hence modify the sub‐arc mantle. Alternatively, hydration and partial melting atop the slab may trigger the formation of composite diapirs composed of partially molten basalt, sediment, and hydrated/serpentinized mantle [ Gerya and Yuen , ; Gerya et al ., ; Gerya and Meilick , ; Zhu et al ., , Zhu et al ., , ; Vogt et al ., ]. Some of these latter studies were examined using laboratory experiments in terms of major element compositions and phase relations [ Castro and Gerya , , Castro et al ., ; Castro et al ., ; Castro et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that preexisting cracks and fissures in initially homogeneous oceanic crust are important factors for clustering of the arc volcanoes. Our initial model with a homogeneous oceanic crust without preexisting cracks and fissures can also produce volcanoes in clusters due to spontaneous clustering of dehydration and melting processes above the slabs driven by water‐induced buoyancy in the mantle wedge [e.g., Zhu et al ., , , ; Honda et al ., ]. That means, preexisting cracks are not a prerequisite for volcanic clustering when we take into account the role of fluid in the subduction zone.…”
Section: Discussionmentioning
confidence: 65%
“…England and Katz [] argued that the arc is located above the place where the boundary defined by the anhydrous solidus makes its closest approach to the trench. In this study, we analyze 3‐D variations in the concentration of mobile water and water release rate in the subduction zone, which reflect the path and source of the fluids/melts in the mantle wedge [e.g., Zhu et al ., ]. Profiles of the mobile water concentration and water release rate for the reference model “Rvp65” and the slow‐subduction‐velocity model “Rvp2” are shown in the fourth and fifth columns of Figures and , respectively.…”
Section: Resultsmentioning
confidence: 99%